Exploring the Implication of ChatGPT AI for Business: Efficiency and Challenges - Md Arman; Umama Rashid Lamiyar (Applied Quantitative Analysis, 2023)
This empirical study examines ChatGPT's impact across various business sectors, evaluating its benefits and challenges. Specifically, the study analyzes how ChatGPT AI transforms business operations and enhances customer experience across customer service, e-commerce, healthcare, finance, marketing, and developer services. Drawing on a comprehensive literature review, this study identifies and analyzes the key applications of AI in the business sector, the benefits realized, and the challenges encountered in its adoption. The study explores the implications of ChatGPT AI for businesses, including its potential to improve efficiency, reduce costs, and enhance competitiveness. Additionally, ethical and legal considerations for the use of ChatGPT AI in business operations are evaluated, including data privacy, bias, and transparency. The study provides insights into future directions for the application of ChatGPT AI in business and the potential impact of this technology on various business sectors. The objective is to provide a comprehensive review of ChatGPT's effects on businesses, its potential benefits, and the challenges companies face when adopting this technology. Overall, this study highlights the importance of considering both the benefits and limitations of AI adoption across industries, as well as its ethical and legal implications.